(untitled) (International Journal of Nursing Education, 2022)
Background: Caregiver strain or burden is a strain experienced by a person who is taking care of a disabled or chronically ill, and an old age person in the family. Caregivers experience burdens in emotional, physical, psychological, economical, and social aspects of their day-to-day life. Objectives: The objective of the study was to identify and compare caregiver strain experienced by them in physical, physiological, social, emotional, and economic areas and to find the association of caregiver strain with selected demographic variables. Methods: Using convenience sampling technique 247 caregivers were recruited in the selected villages of Tapi District, Gujarat. And after obtaining their consent caregivers were interviewed using the caregiver strain index by Robinson BC. Results: 52% of the samples had mild levels of strain, 40% moderate levels, and eight percent of them with severe levels of strain. The economic strain was the highest (54%) and the physiological strain was the least (13%). Relationship with elderly and ability of an elder person to perform Activities of Daily Living had an influence on caregiver strain. Conclusion: Caregiver burden and its impact need to be explored in detail and measures need to be taken to reduce their burden in physical, economical, and emotional areas.